ANALISIS SISTEM TATANIAGA BERAS PANDAN WANGI DI KECAMATAN WARUNGKONDANG, KABUPATEN CIANJUR PROVINSI JAWA BARAT - Eva Yolynda Aviny; Rita Nurmalina; Najmi Anniro (Departemen Agribisnis, FEM-IPB, 2009)
The research was conducted in the production center of Aromatic rice pandan wangi West Java (District of Cianjur) in February-March 2009. The objectives of the study were to analyze the market structure and marketing channel of aromatic rice pandan wangi. The figures used were primary and secondary data with descriptive analysis approach. The result indicated that the marketing system of aromatic rice Pandan wangi build closely into a perfect competition market structure with the shortest marketing channel that involve thraser agent and distributor as the most efficient channel.